Projections of Heat Waves Events in the Intra-Americas Region Using Multimodel Ensemble - Moises Angeles-Malaspina; Jorge E. González-Cruz; Nazario Ramírez-Beltran (Advances in Meteorology)
Significant accelerated warming of the Sea Surface Temperature of 0.15°C per decade (1982–2012) was recently detected, which motivated the research for the present consequences and future projections on the heat index and heat waves in the intra-Americas region. Present records every six hours are retrieved from NCEP reanalysis (1948–2015) to calculate heat waves changes. Heat index intensification has been detected in the region since 1998 and driven by surface pressure changes, sinking air enhancement, and warm/weaker cold advection. This regional warmer atmosphere leads to heat waves intensification with changes in both frequency and maximum amplitude distribution. Future projections using a multimodel ensemble mean for five global circulation models were used to project heat waves in the future under two scenarios: RCP4.5 and RCP8.5. Massive heat waves events were projected at the end of the 21st century, particularly in the RCP8.5 scenario. Consequently, the regional climate change in the current time and in the future will require special attention to mitigate the more intense and frequent heat waves impacts on human health, countries’ economies, and energy demands in the IAR.